STAGES OF LEGAL REGULATION OF INFORMATION INTERMEDIARIES IN THE USA (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
The study of the formation of legal regulation of information intermediaries should begin with the United States. Firstly, it was in the United States that the Internet information and telecommunications network was developed. Accordingly, it was in the United States that the first information intermediaries began to appear, and subsequently the first legal disputes with their participation. Secondly, it was in this country that legal regulation of information intermediaries first arose. Subsequently, the US experience served as the basis for the introduction of this institution in other countries (for example, in the legislation of the EU countries). In turn, the study of the process of introducing the institution of information intermediaries into US legislation will provide an opportunity to better understand the reasons for the emergence of this regulation, as well as the need to improve it at present. The study of the stages of development of legal regulation of information intermediaries in the United States has significant theoretical and practical value. Based on the above, the relevance of this study is obvious.